Case report: Individualized 3D-printed uncemented distal fibular prosthesis preserving the lateral malleolus for repair of distal fibular defects - Xie, Mengzhang; Gong, Taojun; Wang, Yitian; Li, Zhuangzhuang; Zhang, Yuqi; Lu, Minxun; Luo, Yi; Min, Li; Tu, Chongqi; Zhou, Yong (Frontiers in Oncology, 2024)
Background: Involvement of the distal fibula by alveolar soft-part sarcoma is rare.Extensive resection or amputation may be needed; however, distal fibula resection can disrupt foot and ankle biomechanics, leading to ankle joint instability. Reports on joint preservation for maintaining optimal ankle joint function are scarce. Computer-aided design and individualized 3D-printed uncemented implants represent an evolving solution for reconstructing the distal fibula.Case presentation: A 34-year-old woman was diagnosed with alveolar soft-part sarcoma in the right lower leg involving the cortical bone of the fibula. After anlotinib treatment, the tumor size decreased, and the tumor response rate was a partial response (PR); however, the patient continued to experience adverse reactions. With multiple disciplinary team discussions, surgical resection was deemed appropriate. Due to the extensive defect and ankle joint instability after resection, a custom-made 3D-printed prosthesis was designed and fabricated to reconstruct the defect, preserving the lateral malleolus. During the follow-up, the patient achieved favorable ankle function, and no prosthesis-related complications were observed.Three-dimensional (3D)-printed personalized uncemented implants constitute a novel approach and method for addressing the reconstruction issues of the distal fibula and ankle joint. Through the personalized design of 3D-printed prostheses, the lateral malleolus can be preserved, ensuring the normal anatomical structure of the